A note regarding conditioning simulation trials for data-poor management strategy evaluations - E. Punt, André (J. Cetacean Res. Manage., 2019)
Management Strategy Evaluation is a key tool used by the Scientific Committee of the International Whaling Commission to identify appropriate management strategies for commercial and aboriginal subsistence whaling. In several cases, Bayesian approaches have been used to condition the operating models and the assumed priors may substantially impact the conclusions regarding appropriate management strategies in data-poor situations. Three approaches for defining a prior on the ‘scaling’ parameter (on ‘initial depletion’, ‘current depletion’, and ‘carrying capacity’) are compared in terms of the proportion of draws from the prior that are rejected during the construction of the post-model-pre-data distribution and hence the resulting implied distribution for initial and current depletion. Overall, placing a prior on initial depletion leads to the fewest rejected draws but the implied distribution for current depletion depends on the catch history. In contrast, placing a prior on carrying capacity leads to less optimistic distributions for initial and current depletion and perhaps to unreasonably optimistic distributions for MSY. The is sue of the appropriate distribution for the ‘scaling’ parameter in population models should be an explicit component of Management Strategy Evaluation and Bayesian assessments in data-poor situations in general.